The Story of a Ship Journey, Malaria, and the HBB Gene IVS-II-745 Mutation: Circassian Immigration to Cyprus - Ergoren, Mahmut C.; Temel, Sehime G.; Mocan, Gamze; Dundar, Munis (Global Medical Genetics, 2021)
Background During 19th century, the Circassians were secluded from their lands and forced to migrate to Ottoman Empire properties. Approximately 2,346 Circassians were exiled from Istanbul to Cyprus Island. During the deportation journey, many of Circassian passed away in consequence of malaria and unknown reasons. Overall, 1,351 survivor Circassians managed to reach the island, however, many of them had faced with endemic malaria again in Cyprus. An autosomal recessive hematological disorder thalassemia was the second endemic health condition after malaria, whereas thalassemia carriers show resistance to malaria infections.Materials and Methods A large Cypriot family with 57 members whose grandparents were supposed to be in that ship journey has been investigated in this study. Polymerase chain reaction (PCR)–amplification refractory mutation system (ARMS) analysis technique was used for genotyping the HHB gene.Results The human β-globin (HBB) gene c.316–106C > G (IVS-II-745) (II-745) heterozygous variation have been detected.Conclusion Overall, this study is a very good example for a typical natural selection. In this case, one single gene point mutation did not limit survival in the society; natively, it increased their survival changes to form new colonization and the inheritance of the mutation to the next generations.
Keywords: Circassians; β-thalassemia; IVS-II-745; Cyprus; malaria; genetic fitness